Financial Expenditure for the Public Higher Education in Greece and Cyprus during 2015-2019 - Maris, Georgios; Maloina, Stamatia (HAPSc Policy Briefs Series, 2023)
The economic crisis that affected Greece and Cyprus is a period that deserves to be studied and analyzed in various areas of governance. An important period of time namely from the year 2015 to 2019 where the most important events took place. These events affected public higher education in both countries. The purpose of this particular study is to document and compare central bank spending, for both countries, and draw conclusions. The study presents original findings because if we look at earlier researches there are no reports on this specific topic. It helps us get a picture of the whole situation in public higher education. Thus, researchers who study elements of this can enrich their knowledge and future research